Kinetics of Oxidation of Some Substituted Cinnamic Acids by Imidazolium Dichromate in the Presence of Oxalic Acid - VANANGAMUDI, G.; SUBBAIYAN, M.; GOPALAKRISHNAN, M.; THIRUNARAYANAN, G.; SRINIVASAN, S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of some substituted cinnamic acids has been studied in 60 % acetic acid medium. The order of the reaction is found to be one with respect to [oxidant] as well as [oxalic acid] and fractional with respect to substrate concentration and the reaction is acid catalyzed one. Decrease in dielectric constant of the medium decrease the rate of the reaction. The reaction shows zero salt effect. The reaction rate incerases with increase of concentration of manganous sulfate, reaction rate decreases with increase of concentration of aluminium sulphate due to the formation of complex between Al3+ and oxalic acid. The reaction does not induce the polymerization of acrylonitrile. The reactions are carried out at five different tempeatures and the activation parameters have been calculated.